Draft Annual Plan 1976-77 Volume III (Irrigation and Power) Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1975)
The Drainage of part of the Civil Lines is being looked after by the Irrigation and Flood Control Department from some time past. A limited number of schemes have remained in progress during the last few years most of which are intended to be completed during the year 1976-77. Accordingly a provision of Rs. 5.50 lacs is proposed for continuing schemes in order to complete 4 schemes out of 7 in all.
Department of Planning and Development, Government of Jammu and Kashmir